PXR and CAR single nucleotide polymorphisms influence plasma efavirenz levels in South African HIV/AIDS patients - Swart Marelize; Whitehorn Heather; Ren Yuan; Smith Peter; Ramesar Rajkumar S; Dandara Collet (BMC, 2012)
Abstract Background This study investigated variation in NR1I2 and NR1I3 and its effect on plasma efavirenz levels in HIV/AIDS patients. Variability in plasma drug levels has largely led research on identifying causative variants in drug metabolising enzyme (DME) genes, with little focus on the nuclear receptor genes NR1I2 and NR1I3, coding for PXR and CAR, respectively, that are involved in regulating DMEs. Methods 464 Bantu-speaking South Africans comprising of HIV/AIDS patients on efavirenz-based treatment (n=301) and 163 healthy subjects were genotyped for 6 SNPs in NR1I2 and NR1I3. 32 of the 301 patients had their DNA binding domains (DBDs) in NR1I2 and NR1I3 sequenced. Results Significantly decreased efavirenz plasma concentrations were observed in patients carrying the NR1I3 rs3003596C/C and T/C genotypes (P=0.015 and P=0.010, respectively). Sequencing resulted in the discovery of a further 13 SNPs, 3 of which are novel variants in the DBD of NR1I2. There were significant differences in the distribution of NR1I2 and NR1I3 SNPs between South Africans when compared to Caucasian, Asian and Yoruba population groups. Conclusion For the realisation of personalised medicine, PXR and CAR genetic variation should be taken into consideration because of their involvement in the regulation of DMEs.